Simulation Research on Parameters Matching of Vehicle Engine Cooling System Based on AMEsim. Issue 1 (1st December 2022) - Yuan, Zhongrui; An, Tong; Pan, Yulong; Chen, Haishan; Liu, Yali; Zhan, Caidong
Abstract: The engine cooling system equipped on a 1.5T vehicle is regarded as the research object in this article, and the heat dissipation capacity under different working conditions of this vehicle is simulated based on AMEsim software. The simulation results show that the heat dissipation ability of this cooling system is insufficient under extreme high-temperature climbing conditions. Therefore, the component parameters of the cooling system need to be matched again, and the effectiveness of simulation tests is verified based on AMEsim software. The simulation research in this article has certain engineering application value. It can provide guidance for vehicle engineers of the Original Equipment Manufacturer (OEM) to match the parameters quickly in the early development process of the vehicle engine cooling system.